Tetracyclines in Rheumatoid Arthritis: Dual Anti-Inflammatory and Immunomodulatory Roles, Effectiveness, and Safety Insights - Mislav Radić; Andrej Belančić; Hana Đogaš; Marijana Vučković; Andrea Gelemanović; Andrea Faour; Ivan Vlak; Josipa Radić (Antibiotics)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by persistent inflammation, joint pain, and progressive cartilage and bone erosion. Despite advancements in RA management with disease-modifying antirheumatic drugs (DMARDs) and biologics, some patients remain refractory to conventional treatments. Tetracyclines, such as minocycline and doxycycline, exhibit anti-inflammatory and immunomodulatory properties, making them potential supplementary treatments. This narrative review explores their effectiveness, mechanisms of action, safety profiles, and current challenges in RA care. Tetracyclines have demonstrated significant immunomodulatory effects, including the inhibition of pro-inflammatory cytokines and matrix metalloproteinases (MMPs), which are critical in RA pathology. Clinical trials, including double-blind, placebo-controlled studies, have shown efficacy in reducing RA symptoms, particularly in early and refractory cases. However, their use remains limited by inconsistent evidence, small sample sizes, and concerns about antimicrobial resistance. Current guidelines for RA management do not explicitly recommend tetracyclines due to these limitations, although off-label use may be considered in specific cases. The use of tetracycline for RA is restricted by drug interactions causing bacterial resistance alongside unpredictable patient responses, hence the necessity for prudence in its prescription within a clinical setting. To overcome these limitations, the development of safer compounds, in-depth in silico analyses, and integration with personalized medicine approaches are needed. Overall, tetracyclines show promise as adjunct therapies in RA management due to their dual anti-inflammatory and immunomodulatory actions. This review highlights the need for further research to address gaps in evidence, including the development of modified tetracyclines with reduced antimicrobial effects and improved safety profiles, as well as the integration of personalized medicine approaches to optimize patient outcomes.